Interaksi Sosial Keagamaan Pada Masyarakat Desa Kaballokang Pakkabba Kabupaten Takalar - Rahman, Abdul (Universitas Negeri Makassar, 2025)
One of the characteristics of village communities that still survives today is that they strive to always maintain harmony and harmony between each other in the process of social interaction. This article attempts to explore the social life of the people of Kaballokang Pakkabba Village, especially those related to social-religious interactions as the socio-cultural basis of a civilized society. The main problem studied is what underlies the emergence of religious social interaction and how religious social interaction is practiced in Kaballokang Pakkabba Village. To obtain data in order to answer the main problem, data was collected through observation and in-depth interviews. The data that has been collected is then analyzed using narrative techniques, namely examining a combined collection of descriptions of events and phenomena. The data that has been analyzed is then interpreted based on the understanding and experience of the research subjects, which is then presented in descriptive narrative form. The research results show that the emergence of religious social interaction in Kaballokang Pakkabba Village is based on the understanding of religious communities who always uphold the importance of a harmonious life in accordance with their respective religious doctrines. Religious social interaction finds momentum when each religious adherent celebrates their religious holidays.